The research of gas leak from the pipeline - Grudz, V. Ya.; Grudz, Ya. V.; Drin, N. Ya.; Stasiuk, R. B. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2014)
There are presented the research results of gas leak from the pipeline under pressure through a small hole in a thin wall. The analysis of equations of gas flow energy in the process of gas leak allows making under certain assumptions a formula for the mass flow of gas through a small hole in a wall. However, the experience shows that the assumptions significantly distort the actual state of physical process that ultimately leads to uncertainty in the obtained results. In this regard, there are made a number of analytical and experimental studies to assess the adequacy of theoretical statements with restrictions and the actual results of experiments. The result of the research is an adjustment for the theoretical dependence for the mass flow rate of gas, which flows through a small hole from the tank. There is also showed the dependence of the adjustment on the pressure and temperature of gas in the tank.